Vitamin K Antagonist Use and Level of Anticoagulation Control Among Patients at a Tertiary Hospital in Northern Tanzania - Sarah K. Gharib MMed; Abid M. Sadiq MMed; Faryal M. Raza MMed; Sophia S. Muhali MMed; Annette A. Marandu MMed; Norman J. Kyala MMed; Eliasa K. Ndale MMed; Venance P. Maro MMed; William P. Howlett PhD; Elifuraha W. Mkwizu MMed; Nyasatu G. Chamba PhD; Furaha S. Lyamuya MMed; et al. (Journal of Cardiovascular Pharmacology and Therapeutics)
Background Vitamin K antagonists (VKA) continue to be the principal anticoagulants for both the treatment and prevention of venous thromboembolism. The use of VKA often requires regular monitoring to avoid over-anticoagulation and prevent thromboembolic complications. The aim was to determine the indication for VKA use and factors associated with suboptimal anticoagulation control among patients in northern Tanzania. Methods This was a retrospective cohort study that examined the anticoagulation data of patients on long-term VKA from 1 st January 2020 to 31 st December 2022. Eligible participants were those on VKAs for at least 7 days and with at least 3 international normalized ratio (INR) results. The level of anticoagulation control was determined through the calculation of the time-in-therapeutic range (TiTR) using the Rosendaal and the percent of INR in therapeutic range methods. Results TiTR was found to be 17% using the direct method and 16% using the Rosendaal formula. 102 tests out of 365 were within the target range (28%). Absence of health insurance (aRR: 1.24, 95% CI: 1.06-1.44, P  = .007), alcohol consumption (aRR: 1.37, 95% CI: 1.15-1.62, P  < .001), and prolonged intervals between tests of 14 to 28 days (aRR: 1.34, 95% CI: 1.05-1.74, P  = .018) showed association with INR being out of range. Conclusion Patients who achieved target therapeutic anticoagulation control were less than the acceptable 65%. Anticoagulation outcomes were better in patients with frequent INR monitoring and those with health insurance. Alcohol consumption carries a high risk of poor anticoagulation control. Further studies are needed to enforce better INR control.